Changes in tissue free amino acid pools in growing chickens fed thermally treated vetch diets. Issue 2 (23rd May 2013) - Fernández‐Fígares, I.; Nieto, R.; Aguilera, J. F.; Lachica, M.
Summary A three‐day assay was developed to evaluate the effect of autoclaving on protein quality of vetch as an alternative to classical growth methods. Male chickens (n = 10/diet) were given approximately isonitrogenous diets based on raw or autoclaved vetch for 3 days. Samples of plasma, muscle and liver were obtained for free amino acid analysis. Heating vetch depressed growth (11.9 vs. 23.2 g/d; p < 0.05). Plasma methionine and histidine increased (0.05 < p < 0.06), while gluconeogenic amino acids tended to decrease (p < 0.10) after heating. Muscle free amino acids did not change except for a trend to increased methionine (p = 0.06) in birds fed autoclaved vetch. In liver, most essential amino acids, glycine, proline and tyrosine increased markedly with heated vetch diet. Correlations between plasma and muscle free amino acids were poor compared with those between plasma and liver free amino acids. Liver free amino acid pool was more sensitive than muscle or plasma pool to amino acid inflow modifications after vetch heating.